Value of experiments in teaching the natural sciences. science workshop children of the seat of Atlantic University of Costa Rica: an experience to share - Arce Urbina, María Elena (2012)
Since 1997, it has developedHeadquarters Atlantic Coast UniversityRica, the educational-recreational project called"Science Workshop for Children Second Cycle", thewhich has as its main objective, the approach of allowing children and girls to a different system of natural science education, througha more attractive and effective method, based on theexperimentation.The assumption is that science is asBiology, Chemistry and Physics, where we find the answers to a lot of questions that arise when we look at the different phenomena occurring around us. for thiswe do not confine teachingnatural sciences to the board or to dictation.This article will share some of the achievements of these years of work in the shop, and the views of parents of participating children. Also included are the results of asurvey conducted in 2000, to teachers of the city of Turrialba, to get their opinion on whether or not it is important to carry out experiments in science classes.